1987
DOI: 10.1007/bf01812855
|View full text |Cite
|
Sign up to set email alerts
|

The inborn errors of mitochondrial fatty acid oxidation

Abstract: To date, seven inborn errors of mitochondrial fatty acid oxidation have been identified. A total of about 100 patients in the world have been reported. Clinically the beta-oxidation defects are more often characterized by episodic hypoglycaemia leading to a coma mimicking Reye's syndrome. The hypoglycaemia is non-ketotic since the synthesis of ketone bodies is deficient. Periods of decompensation occur when carbohydrate supply is poor, e.g. prolonged fasting, vomiting, or increased caloric requirements, as and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(49 citation statements)
references
References 125 publications
1
48
0
Order By: Relevance
“…Touma and Charpentier (1992) reviewed outcomes for 65 MCADD patients identified upon acute onset of the disease at hospitals who had their MCADD diagnosis confirmed by GCIMS.28 A third study summarized the outcomes of the first 23 reported cases of MCADD in the world (mostly from Europe), which were compiled from published case reports of each individual. 29 The prevalence of clinical symptoms reported for patients in all three studies are summarized in Table 2. It is important to note that there is overlap between the studies referenced in Table 2.…”
Section: Disease Associations Clinical Symptoms and Outcomesmentioning
confidence: 99%
“…Touma and Charpentier (1992) reviewed outcomes for 65 MCADD patients identified upon acute onset of the disease at hospitals who had their MCADD diagnosis confirmed by GCIMS.28 A third study summarized the outcomes of the first 23 reported cases of MCADD in the world (mostly from Europe), which were compiled from published case reports of each individual. 29 The prevalence of clinical symptoms reported for patients in all three studies are summarized in Table 2. It is important to note that there is overlap between the studies referenced in Table 2.…”
Section: Disease Associations Clinical Symptoms and Outcomesmentioning
confidence: 99%
“…Rodents more readily produce butyrylglycine than primates for reasons that remain unclear. However, the production of butyrylglycine as an alternative pathway to eliminate excess butyrylCoA is analogous to the production of suberylglycine and hexanoylglycine in MCAD deficiency (19) and isovalerylglycine in isovaleryl-CoA dehydrogenase deficiency (20) of humans. As discussed for isovaleric acidemia (20), glycine conjugation is a critical alternative pathway and is probably a major factor in determining the clinical severity of the disease.…”
Section: Elution Timementioning
confidence: 99%
“…Only 5-10% of FFA are metabolized by this pathway in ketotic rats (1). However, dicarboxylic acids have recently been shown to be a prominent feature of several diseases, including Reye's syndrome (2)(3)(4), neonatal adrenoleukodystrophy (5), Zellweger's syndrome (5), and defects of fatty acid metabolism (6,7). In Reye's syndrome, dicarboxylic acids make up as much as 55% of the total serum FFA (4).…”
Section: Introductionmentioning
confidence: 99%